Membangun Kesadaran Masyarakat Sebagai Upaya Pencegahan Tindak Pidana Politik Uang Pada Pemilu Serentak 2024 - Fathol Bari (Jurnal Hukum dan Sosial Politik, 2023)
Preventing criminal acts of money politics in general elections is an important effort to maintain election integrity and the sustainability of democracy. The practice of money politics can threaten democratic principles, such as justice, participation and accountability. To overcome this problem, public education, information campaigns and community involvement play a crucial role in building public awareness of the dangers of money politics. This article discusses several key issues related to money politics, including factors that influence people to become involved in money politics, the negative impact of money politics on the integrity of elections and democracy, as well as effective strategies for building public awareness. Apart from that, this article also highlights the important role of public education, information campaigns and community involvement in preventing money politics in the 2024 elections. Through this collaborative effort, it is hoped that the public can be actively involved in honest, fair and transparent elections and avoid the rise of politics. Money.